Time–Course Analysis of the Onset and Progression of Cuticle Cracking in Fruits of Cherry Tomato Cultivar ‘Nene’ - Ryosuke Hosoi; Kazuo Ikeda; Takashi Nishizawa; Tomoyuki Nabeshima (Horticulturae)
Cuticle cracking in tomatoes, characterized by fine cracks on the cuticular membrane, significantly reduces their shelf life. In this study, we collected basic information about the onset and progression of cuticular cracks in cherry tomatoes by observing the time–course of cuticular cracks incidence and severity during three cultivation periods. Several fruit characteristics—including the fruit weight, cuticular membrane deposition, and epidermal cell morphology—were analyzed alongside environmental factors to identify the conditions under which cuticular crack occurs. In the spring–summer season, cuticular cracks’ onset occurred at 30 days after anthesis, whereas in the summer–autumn, it occurred at 20 days after anthesis. The severity of cuticular cracks at harvest was higher in the summer–autumn cultivation than in the spring–summer. These results indicate that the period during which susceptibility to cuticular cracks increases may vary by season, contributing to seasonal differences in the final severity. However, no consistent relationship was observed between the incidence or severity of cuticular cracks and the fruit size, temperature, or humidity throughout the study. In both seasons, the onset of cuticular cracks coincided with the peaking of the cuticular membrane deposition. Thickening of the cuticular membrane, resulting in decreased elasticity may contribute to the cuticular cracks’ onset.